(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
It is established that at T=298 K in aqueous solution and in presence of low concentrations of potassium persulfate (PP) and triethanolamine (TEolA) during some hours acrylic acid (AAc) ([AAc]0=0.5 M) practically completely is polymerized. The polymerization mechanismis is complex. The process occurs gradually. It is assumed that during polymerization the nature of the compound, which stimulates PP homolysis is being changed. In the initial stage that compound is the TEolA. It is established that in aqueous solutions under the action of PP occur the following transformations: TEolA→diethanolamine→ monoethanolamine. Both mono- and diethanolamines separately do not form with PP initiating systems. But they may be condensed with AAc with formation of corresponding tertiary amines, which with PP are able to continue polymerization′s initiation but with less rate.